CONSUMER BUYING BEHAVIOUR: AN EXPLORATORY STUDY DESCRIBING THE IMPACT OF INSTAGRAM INFLUENCER MARKETING WITHIN A SOUTH AFRICAN CONTEXT. - Moodley, Kayleen (The IIE, 2022)
When consumers are looking for reviews and recommendations, they often turn to someone they know who is authentic, shares the same values as them and who is honest (Estay, 2021). It is very rare that a consumer will purchase a product just by taking a stranger’s word for it. This is because the more interaction a consumer has with the product the more comfortable and familiar, they will be when making a purchasing decision (Estay, 2021). And this can be attributed to a combination of Instagram and influencer marketing which generates the right amount of luxury and exposure for brands and products (Estay, 2021). It is for this reason that many brands have turned to Instagram and influencer marketing to help drive marketing campaigns and increase sales through a human touch (Estay, 2021). It was for these reasons that the researcher had taken an interest in the topic and had chosen to centre this dissertation around if and how Instagram influencer marketing impacts consumers buying behaviour. To help understand this phenomenon the researcher conducted four semi-structured in-depth interviews and sent out eleven questionnaires to help support the findings of secondary research. Once all the data was obtained and analysed the researcher discovered that many consumers base their purchasing decision around the reviews and recommendations of the Instagram influencer and the consumers only trusted these reviews and recommendations because they found the Instagram influencers relatable, authentic, and honest. Henceforth, the findings obtained by the researcher imply that Instagram influencer marketing does have an impact on consumer buying behaviour. By the end of this dissertation the reader will be able to determine whether Instagram influencer marketing does impact consumer buying behaviour or whether this phenomenon needs to be researched further to gain a greater depth of knowledge to come to a conclusion.
Keywords: Social media; Buying patterns; Instagram